Detection of SARS-CoV-2 Delta Variant of Concern AY.57 and Clinical Characteristics of Imported Cases on a Vietnamese Coal Carrier Vessel in East Kalimantan, Indonesia: A Case Report - Marwan Marwan; Wira Winardi; Abdul Mu'ti; Sri Wahyuni; Ridmawan Wahyu Jatmiko; Donni Irfandi Alfian; Muhammad Ikhwan Nur; Satria Sewu (Faculty of Medicine Universitas Airlangga, 2022)
Introduction: The 2019 Coronavirus Diseases (COVID-19) continues to be a severe public health issue throughout the world. Disease transmission channels exist across all modes of transportation, including land, air, and water. The presence of this disease has been demonstrated by a study conducted in South Korea, which discovered that 90% of ship passengers have also been tested with SARS-CoV-2 virus. Case: At the port of Samarinda, real-time polymerase chain reaction (RT-PCR) testing was performed on 20 Vietnamese coal carrier vessel crew members. According to the findings obtained from the RT-PCR test, every single member of the team had been infected with the virus. Since they exhibited symptoms of an infection caused by SARS-CoV-2 virus (such as coughing, fever, and shortness of breath), a total of 6 members had to be taken to the hospital. According to the results of genomic sequencing, the crew members were found to be infected with SARS-CoV-2 virus and variant of concern (VOC) of Delta AY.57, Vietnam lineage. Conclusion: COVID-19 can be transmitted via public transportation, including land, air, and sea travel. Controlling the spread of the virus requires RT-PCR testing at terminals, stations, and ports. SARS-CoV-2 Delta variant is still dominating Southeast Asia region, particulary Delta VOC AY.57.